Matrix metalloproteinases in tumor invasion - Łapińska, Joanna (Contemporary Oncology/Współczesna Onkologia, 1999)
One of the processes responsible for tumor cell invasion and metastasis is degradation of the extracellular matrix (ECM) proteins. To overcome the physical barrier, which is ECM, tumor cell produces proteolytic enzymes. A family of metalloproteinases named „matrix metalloproteinases” (MMPs) plays an important role in matrix degradation. Information about MMP and their inhibitors has led to a number of successful inhibitor strategies in tumor treatment.